Activities and impacts of patient engagement in CIHR SPOR funded research: a cross-sectional survey of academic researcher and patient partner experiences - Chudyk, Anna M.; Stoddard, Roger; McCleary, Nicola; Duhamel, Todd A.; Shimmin, Carolyn; Hickes, Serena; Schultz, Annette S. H. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Knowledge about the specific engagement activities pursued and associated impacts of patient engagement in research in Canada remains nascent. This study aimed to describe engagement activities and perceived impacts of projects funded by the Strategy for Patient-Oriented Research (SPOR). Methods This was a cross-sectional online survey of academic researchers and patient partners engaging in projects funded through 13 SPOR funding calls (2014–2019). Patient engagement activities and impacts were measured using a self-developed survey. Thematic analysis was used to describe engagement activities and impacts. Results 66 of 511 academic researchers and 20 of 28 patient partners contacted completed the survey and were included in analyses. Respondents reported that patient partners were engaged in seven types of activities across the research cycle: (a) sharing experiences/giving advice, (b) identifying the research focus/methods, (c) developing/revising aspects of the project, (d) conducting research activities, (e) study participation, (f) presenting on behalf of the project, and (g) other grant development or knowledge translation activities. Engagement was associated with six different types of impacts related to knowledge, outputs, or directions being (a) created, (b) moulded, (c) confirmed, or (d) chosen/prioritized, (e) perceived success of the research, and (f) minimal/negative impacts on the research. Conclusions This study presents information on different ways that patient partners were engaged in SPOR-funded research and the potential impacts of these activities. This knowledge base is imperative to the future of patient engagement in research, including the planning and evaluation of future studies that engage patients as active shapers of research.

Plain English Summary The Canadian Institutes of Health Research developed the Strategy for Patient-Oriented Research (SPOR) to help increase capacity for patient engagement in research. However, little is known about the ways in which Canadian patient co-researchers (i.e., patient partners) are being engaged in research and the perceived impacts of engagement. Therefore, this study aimed to describe engagement activities and perceived impacts of SPOR-funded projects. To do so, we carried out an online survey of academic researchers and patient partners engaging in projects funded through 13 SPOR funding calls. We analysed the collected data using thematic analysis, which focuses on finding themes among data. Sixty-six of 511 academic researchers and 20 of 28 patient partners contacted completed the survey and were included in analyses. We found that patient partners were engaged in seven types of activities across the research cycle: (a) sharing experiences/giving advice, (b) identifying the research focus/methods, (c) developing/revising aspects of the project, (d) conducting research activities, (e) study participation, (f) presenting on behalf of the project, and (g) other grant development or knowledge translation activities. We also found that engagement was associated with six different types of impacts related to knowledge, outputs, or directions being (a) created, (b) moulded, (c) confirmed, or (d) chosen/prioritized, (e) perceived success of the research, and (f) minimal/negative impacts on the research. The findings of this study can be used to inform ongoing and future research, including empowering patient partners to be more informed and actively shape how they may contribute to research processes.